Increased electrode activity during geosmin oxidation provided by Pt nanoparticle-embedded nanocarbon film. Issue 18 (23rd April 2019) - Kamata, Tomoyuki; Sumimoto, Michinori; Shiba, Shunsuke; Kurita, Ryoji; Niwa, Osamu; Kato, Dai
Abstract : The musty odor compound geosmin was electrochemically detected by using Pt nanoparticle (PtNP)-embedded nanocarbon (Pt–C) films formed with unbalanced magnetron (UBM) co-sputtering. Abstract : The musty odor compound geosmin was electrochemically detected by using Pt nanoparticle (PtNP)-embedded nanocarbon (Pt–C) films formed with unbalanced magnetron (UBM) co-sputtering. The sputtered Pt components formed NPs (typically 1.53–4.75 nm in diameter) spontaneously in the carbon films, owing to the poor intermiscibility of Pt with carbon. The surface concentrations of PtNPs embedded in the nanocarbon film were widely controllable (Pt = 4.8–35.9 at%) by regulating the target powers of the Pt and carbon individually. The obtained film had a flat surface ( R a = 0.17–0.18 nm) despite the fact the PtNPs were partially exposed at the surface. Compared with a Pt film electrode, some Pt–C films exhibited higher electrode activity against geosmin although the surface Pt concentrations of these Pt–C films were much lower than that of the Pt film electrode, thanks to the wider potential window and lower background current that resulted from the ultraflat and stable carbon-based film prepared by UBM co-sputtering. Computational experiments revealed that the theoretical oxidation potential ( E ox ) value for geosmin was relatively similar to that obtained in electrochemical experiments using our Pt–C film electrode. Moreover, we also theoretically estimated the possible oxidation site of geosmin molecules and the advantage of the NP shape of the electroactive Pt parts as regards the electrochemical oxidation of geosmin. We successfully used the Pt–C film (10.6 at%) electrode to detect geosmin in combination with HPLC at a low detection limit of 100 ng L −1 .